Dynamic Nanoparticle Assemblies for Biomedical Applications. Issue 14 (22nd February 2017) - Li, Fangyuan; Lu, Jingxiong; Kong, Xueqian; Hyeon, Taeghwan; Ling, Daishun
Abstract : Designed synthesis and assembly of nanoparticles assisted by their surface ligands can create "smart" materials with programmed responses to external stimuli for biomedical applications. These assemblies can be designed to respond either exogenously (for example, to magnetic field, temperature, ultrasound, light, or electric pulses) or endogenously (to pH, enzymatic activity, or redox gradients) and play an increasingly important role in a diverse range of biomedical applications, such as biosensors, drug delivery, molecular imaging, and novel theranostic systems. In this review, the recent advances and challenges in the development of stimuli‐responsive nanoparticle assemblies are summarized; in particular, the application‐driven design of surface ligands for stimuli‐responsive nanoparticle assemblies that are capable of sensing small changes in the disease microenvironment, which induce the related changes in their physico‐chemical properties, is described. Finally, possible future research directions and problems that have to be addressed are briefly discussed. Abstract : Dynamic nanoparticle assembly can create "smart" materials with programmed responses to external stimuli for biomedical applications. The recent advances and challenges in the development of stimuli‐responsive nanoparticle assemblies are shown, along with their diverse range of biomedical applications, such as biosensors, drug delivery, molecular imaging, and novel theranostic systems.